Study of Correlation between different fingerprint Patterns and Emotional intelligence in Medical Students (Journal of Chittagong Medical College Teachers' Association, 2023)
Background: Dermatoglyphics is a field of study that focuses on the patterns of ridges on the skin's surface found on the palms of hands, fingers, and soles of the feet. During development, various creases develop on the brain and are reflected on fingerprints representing various regions of the brain and are commonly being used in dermatoglyphics mental intelligence test. It has been suggested that there is a relationship between dermatoglyphic patterns and various types of intelligence in humans. This study aims to investigate the potential correlation between intelligence level in young individual and dermal ridge pattern.Materials and methods: This study was conducted in the Department of Anatomy, Chattagram Maa-O-Shishu Hospital Medical College from November 2021 to May 2022. Sample were collected from Chattagram Maa-O-Shishu Hospital Medical College. Self-evaluating questionnaire was applied on 95 M.B.B.S. students of Phase I. The subjects were categorized into two groups- Category A including subjects with EQ>120 and Category B including subjects with EQ120 and 83% population scored EQ